2015
DOI: 10.1074/jbc.m115.679738
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory and Kinase Domains but Not the Interdomain Linker Determine Human Double-stranded RNA-activated Kinase (PKR) Sensitivity to Inhibition by Viral Non-coding RNAs

Abstract: Background: Human PKR (hPKR) interdomain linker (IDL), regulatory domain, and kinase domain contributions to RNA-mediated regulation are incompletely defined. Results: Whereas the IDL plays no role, both domains are involved in RNA-mediated inhibition. Conclusion: hPKR susceptibility to viral RNA inhibitors is dictated by determinants in both domains. Significance: Human viruses evolved non-coding RNA features specific to potent hPKR inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 51 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Similarly, Conn and coworkers that reported that removal of the linker did not block activation of PKR by dsRNA or inhibition by VAI RNA. 16 They found that the functional properties of hPKR and a linker-deleted construct are identical, whereas we detected some quantitative differences in RNA-independent and dependent activation and RNA binding affinities. Interestingly, rat PKR was reported to bind viral RNA inhibitor with the same affinity as the human enzyme but the inhibition potency was greatly reduced.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similarly, Conn and coworkers that reported that removal of the linker did not block activation of PKR by dsRNA or inhibition by VAI RNA. 16 They found that the functional properties of hPKR and a linker-deleted construct are identical, whereas we detected some quantitative differences in RNA-independent and dependent activation and RNA binding affinities. Interestingly, rat PKR was reported to bind viral RNA inhibitor with the same affinity as the human enzyme but the inhibition potency was greatly reduced.…”
Section: Discussionmentioning
confidence: 52%
“…Indeed, it was recently reported that deletions of the linker region from hPKR do not affect dsRNA binding, activation or inhibition by noncoding viral RNA inhibitors. 16 …”
mentioning
confidence: 99%
“…We next tested the effect that these differences in PKR binding had on the ability of each nc886 conformer to inhibit PKR autophosphorylation in the presence of a dsRNA activator using an established slot-blot radiometric kinase assay (Sunita et al 2015). PKR autophosphorylation was measured in the presence of a fixed concentration of poly(rI:rC) dsRNA and increasing amounts of each nc886 RNA conformer.…”
Section: Nc886 Rna Conformers Have Opposing Activities Against Pkrmentioning
confidence: 99%
“…PKR activation assays PKR (0.1 μg) was incubated with 0-10 μM of full-length or variant nc886 RNA for 10 min at 25°C in 50 mM Tris buffer (pH 7.8) containing 50 mM KCl, 2.5 mM DTT, 10% glycerol, 20 μM ATP, 1 μCi [γ 32 P]-ATP, and 2 mM MgCl 2 . After incubation, reactions were quenched with excess ice-cold phosphate buffered saline containing 200 μM ATP and applied to a Bio-Dot SF (Bio-Rad) microfiltration system as described previously (Sunita et al 2015). Membranes were exposed to a phosphor storage screen and the extent of phosphorylation was determined using analysis by a Typhoon FLA 7000 PhosphorImager and ImageQuant software (GE Healthcare).…”
Section: Pkr Inhibition Assaysmentioning
confidence: 99%
“…PKR exists in an ensemble of extended and compact conformations (Anderson and Cole 2008;VanOudenhove et al 2009). Interestingly, removal of this interdomain linker did not abolish dsRNA-dependent autophosphorylation nor inhibition by viral RNAs in vitro (Sunita et al 2015;Husain et al 2016). However, the linker's carboxy-terminal portion, a 23-a.a. "basic patch," is required for full activation and enhances PKR's basal activity (Husain et al 2016).…”
Section: Bridging the Regulatory And Effector Domainsmentioning
confidence: 99%